The Soil Classification course in Russian universities: an important ingredient of education - Gerasimova, Maria; Bezuglova, Olga Stepanovna (Bulletin of Geography. Physical Geography Series, 2018)
Teaching soil classification in the universities of Russia is discussed as a rather new experience in the education of specialists in environmental science. The lecture courses (24-30 academic hours) change following the inevitable changes in soil classification systems. As introduction, an outline of objectives and structure of soil classifications is given followed by a brief overview of most known national systems, which is also important for understanding the difficulties, origin and problems of the International WRB system. The latter is the central point of the course, its principles are explained, main diagnostic features of RSGs are communicated, and students are trained to use it basing on the descriptions of soil profiles and analytical data to them. In conclusion, the reasons to know and to work with soil classifications are specified as for future soil scientists, so for specialists in environmental science.